Digitalization of the Tax System in Indonesia: Opportunities and Challenges of Coretax Implementation - Uli Lasdao Mara; Agus Munandar (Universitas KH. Abdul Chalim Mojokerto, 2025)
The digitalization of the tax system represents a strategic initiative by the government to enhance the effectiveness and efficiency of tax management. A key innovation in this effort is the implementation of the Coretax system, which modernizes tax administration through information technology in areas such as tax reporting, payments, and oversight. This study aims to examine how the Coretax system contributes to the success of tax management in Indonesia and to identify the opportunities and challenges associated with its implementation in the digital era. The research employs a qualitative approach using literature review methods, analyzing secondary data sourced from scientific journals, official reports from the Directorate General of Taxes (DGT), and academic publications and policies related to tax digitalization. Through thematic analysis, the study describes the impacts, benefits, and challenges experienced in the application of the Coretax system. The findings indicate that Coretax improves the accuracy and efficiency of tax administration, strengthens fiscal oversight, and increases transparency within the Tax Information System. However, several implementation challenges persist, including issues related to digital literacy, technological infrastructure, human resource capacity, and data security risks, all of which require proactive management. To ensure the optimal implementation of Coretax and support a modern, transparent, and accountable public taxation system in Indonesia, integrated and harmonized policies are essential.